Drug resistance and pathogenicity characteristics of Escherichia coli causing pneumonia in farmed foxes - Zhang, Chunxiao; Li, Hong; Zhao, Qi; Wang, Lili; Hou, Guanxin; Shi, Qiumei; Wu, Tonglei; Gao, Guangping; Zhang, Zhiqiang (Frontiers in Veterinary Science, 2025)
Bacterial pneumonia is a leading cause of mortality in fur-bearing animals, posing significant threat to fur production. To clarify the pathogenic agent of bacterial pneumonia in farmed foxes from eastern Hebei province, China, we performed bacterial isolation and identification from samples between 2020 and 2023. A total of 142 bacterial strains were isolated, of which 101 were identified as Escherichia coli (E. coli), indicating that E. coli is the major cause responsible for bacterial pneumonia in farmed foxes. Serotyping identification showed that a total of 8 serotypes were prevalent in the E. coli isolates, with O1, O8, O78 and O12 being the dominant ones. Five E. coli isolates were randomly picked for pathogenicity testing, and all of them were able to cause pneumonia symptoms in 6-week-old Kunming mice, accompanied by organ damage in lung. Eleven virulence genes were demonstrated present among the E. coli isolates. Antibiotic susceptibility tests showed that 78 of 101 E. coli strains exhibited multi-drug resistance (MDR), with the highest resistance rates against tetracyclines, and some strains showed resistance to carbapenems. Notably, no single antibiotic was effective against all strains. Twenty antibiotic resistance genes (ARGs) were detected among the isolates. Multilocus sequence typing (MLST) revealed 11 sequence types (STs) among 19 E. coli isolates, with ST-101 predominating (4/19). These findings enhance our understanding of the epidemiology, resistance traits, and pathogenicity of fox-derived pathogenic E. coli in Hebei.